2019
DOI: 10.3390/molecules24112103
|View full text |Cite
|
Sign up to set email alerts
|

Novel Targeted Nano-Parthenolide Molecule against NF-kB in Acute Myeloid Leukemia

Abstract: The targeted nano-encapsulation of anticancer drugs can improve drug delivery and the selective targeting of cancer cells. Nuclear factor kappa B (NF-kB) is a regulator for different biological responses, including cell proliferation and differentiation. In acute myeloid leukemia (AML), constitutive NF-κB has been detected in more than 50% of cases, enabling leukemic cells to resist apoptosis and stimulate uncontrolled proliferation. We evaluated NF-kB expression in bone marrow samples from 103 patients with A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(44 citation statements)
references
References 54 publications
1
43
0
Order By: Relevance
“…The results of the in vivo study indicated that nanocarriers can significantly and selectively facilitate tumor reduction [86]. Similar promising results were also shown in other studies, for example in the use of docetaxel nano-targeted delivery for the treatment of prostate cancer, use of NDAT for the targeted delivery of paclitaxel, cisplatin, and doxorubicin in tumor xenografts and in the delivery of toremifene in prostate cancer [87][88][89][90][91].…”
Section: Nanopharmaceuticalssupporting
confidence: 83%
See 1 more Smart Citation
“…The results of the in vivo study indicated that nanocarriers can significantly and selectively facilitate tumor reduction [86]. Similar promising results were also shown in other studies, for example in the use of docetaxel nano-targeted delivery for the treatment of prostate cancer, use of NDAT for the targeted delivery of paclitaxel, cisplatin, and doxorubicin in tumor xenografts and in the delivery of toremifene in prostate cancer [87][88][89][90][91].…”
Section: Nanopharmaceuticalssupporting
confidence: 83%
“…Active nano-targeting for tumor-targeted delivery could be achieved using high-affinity ligand for a unique target that is overexpressed by cancer cells and their associated microenvironment, such as the case with integrin αvβ3, PSMA, or CD44 for delivery of chemotherapy into specific tumors [85][86][87][88][89][90][91]. Nanotechnology has been studied in vitro and in vivo to potentially restrict the action of the anti-angiogenic agent, diamino tetraiodothyroacetic acid (DAT) to the integrin avβ3 by conjugating DAT to PLGA NPs, forming DAT-conjugated PLGA (NDAT).…”
Section: Nanopharmaceuticalsmentioning
confidence: 99%
“…Silver nanoparticles synthesized from Moringa oleifera leaf extract inhibited AML Kasumi-1 cell growth with IC50 of 7.5 μ g/ml after 72-hour treatment [ 46 ]. Furthermore, PLGA-antiCD44-PTL nanoparticles inhibited the Kasumi-1 leukemic cells by decreasing its viability by 40% [ 47 ]. In addition, Li et al [ 48 ] reported that CD33-targeted lipid nanoparticles (aCD33LNs) they synthesized effectively delivered GTI-2040 to the intended target to inhibit the proliferation of Kasumi-1 cells.…”
Section: Resultsmentioning
confidence: 99%
“…Besides new derivatives of PN with better bioavailability, alternative delivering systems are in the focus of current research. Encapsulation into the micelles, drug-loaded nano-vectors or nanographene delivery [16,[203][204][205][206] might allow to exploit the full spectrum of the anticancer activities of PN and may be crucial for the development of new combination therapies.…”
Section: Discussionmentioning
confidence: 99%